A CONCEPTUAL FRAMEWORK OF PRODUCT-SERVICE SYSTEMS DESIGN FOR SUSTAINABILITY TRANSITIONS. (May 2020) - Mitake, Y.; Hiramitsu, K.; Nagayama, A.; Muraoka, N.; Sholihah, M.; Shimomura, Y.
Abstract: Product-service systems (PSSs) are regarded as one of the promising ways to contribute to a sustainable society. Despite the well-developed knowledge, PSS design lack of long-term perspective to treat related changes and uncertainties. To address this issue, this paper proposes a conceptual framework of sustainable PSS design for sustainability transition by integrating insight from design approach for system innovation and transition. Applicability of the proposed framework is illustrated through application to example of PSS development project for wildlife nuisance in a suburban city.